Age-Related Frontal Periventricular White Matter Hyperintensities and miR-92a-3p Are Associated with Early-Onset Post-Stroke Depression - He, Ji-Rong; Zhang, Yu; Lu, Wen-Jing; Liang, Huai-Bin; Tu, Xuan-Qiang; Ma, Fei-Yue; Yang, Guo-Yuan; Zeng, Li-Li (Frontiers in Aging Neuroscience, 2017)
Objective: To explore the correlationship among white matter hyperintensities (WMHs), miR-92a-3p and early-onset post-stroke depression (PSD). Methods: We recruited consecutively 238 patients with acute cerebral infarction and MRI examination in the Department of neurology, Ruijin hospital, Shanghai Jiaotong University School of Medicine. The diagnosis of early-onset PSD was made in accordance with DSM-IV criteria for depression in 2 weeks after stroke. Clinical information and assessments of stroke severity were recorded on admission. The analysis of plasma miR-92a-3p was performed using quantitative PCR at the same time. WMHs were evaluated by the Fazekas and Scheltens visual rating scales. The relationship among WMHs, miR-92a-3p and PSD were analyzed by SPSS 22.0 software. Results: Logistic regression demonstrated that periventricular WMHs (PVWMHs) in frontal caps was an independent risk factor with early-onset PSD (OR=1.579, 95% CI: 1.040-2.397, p=0.032). The age and numbers of lacunes were related to frontal PVWMHs. Plasma miR-92a-3p in the PSD group was higher compared with the non-depressed group. ROC analysis revealed that miR-92a-3p could predict early-onset PSD with 90% sensitivity and 90% specificity. The higher miR-92a-3p trended toward association with greater frontal PVWMHs. Conclusion: Acute ischemic stroke patients with frontal PVWMHs or a high plasma miR-92a-3p at baseline were more likely to develop early-onset PSD. MiR-92a-3p might be involved in the white matter impairment and post-stroke depression.